PREDICTING THE VARIABILITY IN THE WAVELENGTH STRUCTURES OF THE INCOMING RADIATION DUE TO OZONE LAYER DEPLETION AT ARABIAN SEA - K. Yousaf Zai, M. A.; Quamar, J.; Iqbal, J.; K. Ansari, M. R.; Hussain, M. A. (The Nucleus, 2010)
In this communication we have investigated the variability in the wavelength structures of the radiation due to ozone layer depletion (OLD) using empirical modeling approach. A model has been developed for evaluating sea surface temperature using stratospheric ozone filter. This filter has been formulated taking into account of the ozone layer depletion (OLD) strategy for Pakistan atmospheric regions. For making predictions of various wavelength, stochastic analysis is implemented here for observing future prospects of the coming radiation. These predictions are useful for public, private and government organizations.